Implementación de lavandería en el sector ciudadela El Chorrillo - Proaño León, Derian Eduardo (2020)
Today you live in an accelerated world where time has become an important and highly appreciated factor, every second that passes is a penny earned or lost, people's time is limited and the use of clothing and other clothing is constant That is why they have the need to wash them daily becoming an eternal action. It is based on this concept that the idea of implementing this project arises which will be aimed at providing a washing service with a plus of home removal and delivery service that is considered attractive to all, causing customer satisfaction to use the time they were going to invest in moving to the laundry in other activities